An approach using Caenorhabditis elegans screening novel targets to suppress tumour cell proliferation - Mao, Yu‐Qin (Cell Prolif, 2020)
OBJECTIVES: Tumour cell proliferation requires high metabolism to meet the bioenergetics and biosynthetic needs. Dauer in Caenorhabditis elegans is characterized by lower metabolism, and we established an approach with C elegans to find potential tumour therapy targets. MATERIALS AND METHODS: RNAi screening was used to find dauer‐related genes, and these genes were further analysed in glp‐1(−) mutants for tumour‐suppressing testing. The identified tumour‐related genes were verified in clinical tumour tissues. RESULTS: The lifespan of glp‐1(−) mutants was found to be extended by classical dauer formation signalling. Then, 61 of 287 kinase‐coding genes in Caenorhabditis elegans were identified as dauer‐related genes, of which 27 were found to be homologous to human oncogenes. Furthermore, 12 dauer‐related genes were randomly selected for tumour‐suppressing test, and six genes significantly extended the lifespan of glp‐1(−) mutants. Of these six genes, F47D12.9, W02B12.12 and gcy‐21 were newly linked to dauer formation. These three new dauer‐related genes significantly suppressed tumour cell proliferation and thus extended the lifespan of glp‐1(−) mutants in a longevity‐ or dauer‐independent manner. The mRNA expression profiles indicated that these dauer‐related genes trigged similar low metabolism pattern in glp‐1(−) mutants. Notably, the expression of homolog gene DCAF4L2/F47D12.9, TSSK6/W02B12.12 and NPR1/gcy‐21 was found to be higher in glioma compared with adjacent normal tissue. In addition, the high expression of TSSK6/W02B12.12 and NPR1/gcy‐21 correlated with a worse survival in glioma patients. CONCLUSIONS: Dauer gene screening in combination with tumour‐suppressing test in glp‐1(−) mutants provided a useful approach to find potential targets for tumour therapy via suppressing tumour cell proliferation and rewiring tumour cell metabolism.